The Effects of Three L2 Vocabulary Learning Methods Through Reading Activity - Kodama, Keita; Shirahata, Tomohiko (Beyond Words, 2021)
This study examines the effectiveness of the three vocabulary learning methods the authors adopted. In search of this research issue, the study used longitudinal experiments with 93 university Japanese learners of English (JLEs) for fifteen weeks. Once a week for six consecutive weeks, participants of the three experiment groups were given different treatments for learning 110 targeted English words when they were mainly reading an English textbook: (i) Group A: the Implicit Vocabulary Learning Group with Questions in English/Answers in English Task, (ii) Group B: the Explicit Vocabulary Learning Group with a Cloze Test Task, and (iii) Group C: the Explicit Vocabulary Learning Group with Multiple-choice Word Test Task. A pretest, immediate posttest, and delayed posttest were conducted. The results showed that (i) all the groups improved their performances at the immediate posttest and almost maintained their performance levels at the delayed posttest, which indicate that all the learning methods were more or less effective. However, the developmental degrees of the vocabulary increase were different: Group C showed the highest improvement among the three. From these findings, the authors claim that using a (multiple-choice) word test is fairly effective for JLEs to develop their knowledge of English words.